The concept "nursing" in Greece: a focus group approach - Sapountzi-Krepia, Despina; Dimitriadou, Alexandra; Sakellari, Evanthia; Psychogiou, Maria; Krepia, V.; Raftopoulos, Vasilios (My University, 2007)
The aim of the article was to explore the concept of nursing in Greece through the perceived meaning of the word nursing among nurses and nursing students and to form a definition of the term "nursing".
Keywords: Nursing science; Art; Nursing social status; Nursing as a science and art